2005
DOI: 10.1097/01.cad.0000173474.82486.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of androgen deprivation therapy in the thyroid function test of patients with prostate cancer

Abstract: We have assessed the effect of androgen deprivation therapy (ADT) in the thyroid function test in prostate cancer patients. Serum levels of tri-iodothyronine (T3), thyroxine (T4), free thyroxine (FT4) and thyroid-stimulating hormone (TSH) were determined in a cross-sectional study that included 279 patients diagnosed with prostate cancer. A subset of 96 patients free of prostate-specific antigen relapse after radical prostatectomy became a control group and 183 patients under continuous ADT formed the study gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
4
7
0
1
Order By: Relevance
“…These fi ndings are similar to those of androgen deprived men [9] . Testosterone defi ciency in iodine defi cient rats enhanced increase in serum TSH and thyroid enlargement and caused further decrease in serum-free T 4 induced by iodine defi ciency.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These fi ndings are similar to those of androgen deprived men [9] . Testosterone defi ciency in iodine defi cient rats enhanced increase in serum TSH and thyroid enlargement and caused further decrease in serum-free T 4 induced by iodine defi ciency.…”
Section: Discussionsupporting
confidence: 90%
“…Morote et al considered the eff ect of androgen deprivation therapy (ADT) in the thyroid function tests of patients with prostatic cancer, and demonstrated that ADT alters thyroid function tests. A statistically signifi cant increase in serum TSH level and a decrease in free T 4 were found in patients under ADT [9] . Changes observed in thyroid volume and serum T4, FT4, T3 and TSH concentrations in iodine defi cient as compared to normal rats are similar to previous reports [2,12] .…”
Section: Discussionmentioning
confidence: 95%
“…A small but statistically significant increase in TSH levels (1.81 mU/L in ADT cases, 1.58 mU/L in controls, p = 0.007) and decrease in free thyroxine levels (1.18 ng/dL versus 1.24 ng/dL, respectively, p = 0.018) were noted. Although Salminen et al hypothesized that LHRH agonists may have some previously uncharacterized activity upon the TSH receptor [114], Morote et al correctly pointed out that the clinical significance of a small increase in TSH levels is dubious [115]. The limited available data do not suggest routine monitoring of thyroid function tests is warranted in men undergoing ADT, although further studies are needed.…”
Section: Thyroid Dysfunctionmentioning
confidence: 92%
“…A preliminary report of ten men with advanced prostate cancer found declines in free triiodothyronine (T3) levels but not free thyroxine (T4) levels over a 12-month period [113]. Two groups more recently explored this issue using case-control designs [114,115]. Salminen et al prospectively measured levels of thyroid stimulating hormone (TSH), free thyroxine, and thyroid binding globulin (TBG) in 35 men on ADT and compared it to 36 men undergoing radiotherapy alone [114].…”
Section: Thyroid Dysfunctionmentioning
confidence: 96%
See 1 more Smart Citation